Thiamine and Foliar Hyponex Improve Acclimatization of Coelogyne rochusseni Plantlets in an NFT System - Elfi Indrawanis; Pebra Heriansyah (Agro Bali : Agricultural Journal, 2026)
The Coelogyne rochusseni orchid, an endemic orchid from the island of Sumatra, has beauty and potential for development. The purpose of this research is to explain the physiological mechanisms in increasing the growth and adaptation of orchid plants at the acclimatization stage using the NFT hydroponic system by spraying thiamine and hyponex fertilizer. The design used in this study was a factorial complete randomized design (CRD) consisting of two factors, spraying thiamine and hyponex fertilizer, each treatment consisting of 4 treatment levels, thiamine 0, 1, 2, 3 mg L-1 and hyponex 0,1, 2, 3 mg L-1. 48 total plantlets analyzed and 3 replicates.  The results of the research on acclimatization of the Coelogyne rachusseni orchid plantlets can be concluded that spraying thyamin and hyponex fertilizer as a single factor significantly affected all growth parameters, plant height (cm), leaf length (cm), number of roots (n),percentage of plantlets life (%) with an optimal concentration of 2 mg L-1 and in terms of interaction factors significantly affected the parameter of Percentage of live plantlets with an optimal concentration being a combination of 2 mg L-1 thiamine and mg L-1 hyponex.